Which insights can gas diffusion electrode half-cell experiments give into activity trends and transport phenomena of membrane electrode assemblies? - Schmitt, Nicolai; Schmidt, Mareike; Mueller, Jonathan E.; Schmidt, Lasse; Trabold, Michael; Jeschonek, Katharina; Etzold, Bastian J.M. (Energy Advances, 2023)
Gas diffusion electrode (GDE) half-cell setups were recently presented as a powerful tool to characterize oxygen reduction reaction (ORR) catalyst layers at fuel cell relevant potentials and current densities. In order to pave the way for a broad-based application of the technique, it is essential to assess the comparability of the GDE half-cell technique and real membrane electrode assembly (MEA) measurements. In order to face this concern, we investigate the transferability of trends from GDE half-cell experiments, in which the catalyst layer directly faces the liquid electrolyte, to MEA experiments with (i) an ionic liquid modified and unmodified Pt/C catalyst and (ii) Pt/C catalysts with and without nitrogen modified carbon support at different ionomer to carbon ratios. We show that GDE half-cell experiments can be used to reliably predict trends in catalytic activity for catalyst layers in real MEAs that are related to differences in oxygen mass transport. However, differences in catalytic activity being related to proton accessibility cannot be captured completely due to the differing interphase solid catalyst/liquid electrolyte in GDE testing and solid catalyst/solid electrolyte in MEA testing. In order to account for this, it may be necessary to introduce an ionomer between the catalyst layer and the liquid electrolyte during GDE evaluation, which would, however, dramatically increase the effort required to perform measurements. On the other hand, GDE testing with the catalyst layer being in direct contact with the liquid electrolyte is nevertheless of interest, because it allows for the study of oxygen mass transport properties at application-oriented current densities independent of other transport phenomena.
CRIS-Team Scopus Importer:2023-08-15